Phosphorus availability in dry and high-moisture sorghum grain for growing swine and chicks - M Trotter; G Allee (Kansas Agricultural Experiment Station Research Reports, 1979)
We used 117 crossbred pigs and 260 male White Leghorn chicks to determine the availability of phosphorus in high-moisture sorghum grain treated with propionic acid or stored in an oxygen limiting structure, and in field-dried sorghum grain. Bone breaking force as the criterion in the pig studies and tibia bone ash as the criterion in the chick studies gave availability estimates of 19, 42, and 43% for the pig and 25, 46, and 48% for the chick for dry, HMPA and HMO2L, respectively.; Swine Day, Manhattan, KS, November 8, 1979
Keywords: Swine day; 1979; Kansas Agricultural Experiment Station contribution; no. 80-136-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 371; Swine; Phosphorus; Dry soghum; High-moisture sorghum; Growing chicks